2003
DOI: 10.31610/zsr/2002.11.2.397
|View full text |Cite
|
Sign up to set email alerts
|

Notes on zoogeography and taxonomy of the badgers (Carnivora: Mustelidae: Meles) and some of their fleas (Siphonaptera: Ceratophyllidae: Paraceras)

Abstract: A comparative morphological analysis of the fleas from the melis-flabellum species group of the genus Paraceras (Siphonaptera, Ceratophyllidae) is undertaken. Differences in the structure of the clasper and the 8th tergite allow considering P. melis and P. flabellum separate species. Morphological characters of the Japanese form of Paraceras make possible to treat it as an independent taxon. The distribution ranges of three badger species of the genus Meles (Carnivora, Mustelidae) are shown to correspond to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The common weasel, M. nivalis, Linnaeus, 1766 was first described in Sweden. There is no general approval of the common weasel taxonomy, due to the question of the number of weasel subspecies and species in Africa, Europe, and Asia [10] . The larger-sized weasel (previously called M. nivalis subpalmata) presents in Egypt and attains maximum sizes more than M. nivalis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The common weasel, M. nivalis, Linnaeus, 1766 was first described in Sweden. There is no general approval of the common weasel taxonomy, due to the question of the number of weasel subspecies and species in Africa, Europe, and Asia [10] . The larger-sized weasel (previously called M. nivalis subpalmata) presents in Egypt and attains maximum sizes more than M. nivalis.…”
Section: Resultsmentioning
confidence: 99%
“…Van Zyll de Jong [2] previously observed this difference in the Egyptian weasel size. After using the UPGMA dendrogram, Abramov and Baryshnikov [10] reported that the small-size weasels are presented in one cluster, the average-size weasels in another cluster, and all large sizes comprise the third cluster. The Egyptian weasel is separated from its other members and also placed in the third cluster.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the number of ermine subspecies remains contentious, we chose to assess the most diverse estimates (Hall, 1951), hypothesizing that a subset therein (as proposed by Corbet, 1978or King, 1983) would be identified as distinct. Ermine are strongly sexually dimorphic (Hall, 1951;King, 1983); therefore, following Abramov and Baryshnikov (2000) we restricted morphological sampling to males only, as species diagnosis within mustelids remains consistent even when sex is unknown (Bornholdt et al, 2013). Crania were loaned from the University of New Mexico Museum of Southwestern Biology (MSB), the University of Alaska Museum of the North (UAM), the Museum of Vertebrate Zoology (MVZ) at the University of California Berkley and the Smithsonian National Museum of Natural History (USNM).…”
Section: Geometric Morphometric Methodsmentioning
confidence: 99%